Technical efficiency and equity effects of environmental payments in Ireland - Miguel Angel Tovar Rea\~nos; Maria Martinez Cillero (The Economic and Social Research Institute (ESRI), 2021)
We investigate the relationship between farm level competitiveness and environmental performance using Stochastic Frontier Analysis (SFA). We use an Irish panel of farm level financial data for the years 2000-2017 to analyse the link between EU Common Agricultural Policy environmental payments, and dairy and beef production from economic and environmental views. Our estimates identify a positive relationship between technical efficiency and environmental payments in place in recent years, although not for early versions of these payments. We simulate increases in the Green, Low-Carbon, Agri-Environment payments targeted to farms with low stocking rates, financed through reductions in decoupled payments. We find that under this stylised scenario, competitiveness and environmental gains are achieved for dairy farms. However, under this scenario, we do not identify gains for beef farms. We also find a reduction in income inequality under this scenario for both farm types.
Keywords: Q12; Q18; Q52; 330; Stochastic Frontier Analysis; emissions; income inequality; agricultural subsidies; technical efficiency; simulation